What’s the matter in phytoplankton? Highlighting the importance of stoichiometric traits in lake ecosystem models - Olson, Carly R.; Gschwentner, Daniel; Drost, Annemieke M.; Mohan, Joseph; Klip, Helena C. L. (Frontiers in Ecology and Evolution, 2024)
IntroductionAccurate models of lake primary production are crucial for understanding ecosystem function and predicting ecosystem responses to global change. However, current research in lake ecosystem modeling has emphasized environmental characteristics while less work has considered phytoplankton stoichiometric traits. Importantly, these traits link resource availability to primary production via organismal metabolism and thus are critical to predicting ecosystem function.MethodsHere, we use an existing database of phytoplankton traits and lake ecosystem models to demonstrate that phytoplankton minimum quotas for nitrogen and phosphorus significantly influence predictions of lake gross primary production. Additionally, we compare how different parameterizations of phytoplankton stoichiometry affect modeled gross primary production. Finally, we evaluate the ability of the models to capture observed patterns in gross primary production and seston stoichiometry for lakes in the Northern Hemisphere.Results and discussionWe argue that parameterization and calibration of phytoplankton stoichiometric traits will improve lake ecosystem models and are critical for obtaining better estimates of lake primary production.